The Effects of Teacher Feedback and Automated Feedback on Cognitive and Psychological Aspects of Foreign Language Writing: A Mixed-Methods Research - Wang, Zehua; Han, Feifei (Frontiers in Psychology, 2022)
Feedback plays a crucial role in the writing processes. However, in the literature of foreign language (FL) writing, there is a dearth of studies which compare the effects of teacher feedback and automated feedback on both cognitive and psychological aspects of FL writing. To fill this gap, the current study compared the effects of teacher feedback and automated feedback on both revision quality and writing proficiency development (ithe cognitive aspects); and perceived usefulness and perceived ease of use of the feedback (the psychological aspects) in English writing among English learners as a FL (EFLs) in China. It also investigated students’ perceptions of the strengths and weaknesses of the two types of feedback. The study adopted a mixed-methods design. The quantitative method collected the data through 1) a pre-test and a post-test, which measured the participants’ English writing proficiency development; 2) a writing task, which received either teacher feedback or automated feedback; and 3) a close-ended questionnaire, which examined students’ perceived usefulness and perceived ease of use of the feedback. The qualitative method collected the data through an open-ended questionnaire, which examined the participants’ perceptions of the strengths and weaknesses of teacher feedback or automated feedback depending on the type of the feedback they received. Chinese university EFLs in two English classes (n = 35 in each class) taught by the same English teacher participated in the study: one class received teacher feedback whereas the other received automated feedback using Pigaiwang. While the students in the two classes did not differ significantly on the pre-test of students’ writing proficiency; students who received teacher feedback scored significantly higher on revision than those who received automated feedback. Students in the teacher feedback class also had significantly higher ratings on perceived usefulness and perceived ease of use of the feedback than those in the automated feedback class. However, students in the automated feedback class obtained significant higher scores on the post-test of the writing proficiency. The qualitative results identified three themes of strengths and two themes of weaknesses for the teacher feedback and the automated feedback respectively.